ANALISIS UPAYA PENINGKATAN MUTU MANAJEMEN PELAYANAN BENCANA TERHADAP KORBAN BENCANA DI RS PKU MUHAMMADIYAH BANTUL BERDASARKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Dyah Mustika Kurniatri; Sunaryadi Sunaryadi (Universitas Muhammadiyah Yogyakarta, 2016)
Background: Hospitals must be well prepared and ready for any kind of disaster in both of its facilities and human resources. PKU Muhammadiyah Bantul Hospital is situated within disaster prone area. The main issues faced by the hospital are complaints from disaster victims regarding its medical services, nursing, and medical facilities. Therefore, PKU Muhammadiyah Bantul Hospital tries to make serious efforts to improve its service quality by conducting a deep analysis of patients. Method: The Quality Function Deployment (QFD) method is applied to measure the service quality improvement in PKU Muhammadiyah Bantul Hospital. This method mainly formulates the management’s improvement efforts based on demands. Subjects of this research were earthquake’s victims at Yogyakarta in 2006 with 30 people as the samples. Result and discussion: House of Quality analysis in QFD recommends several improvements that are required by PKU Muhammadiyah Bantul Hospital regarding medical services, nursing and other supporting facilities: 1. Medical personnel excellence training; 2. Physician competency assessment; 3. Medical personnel’s respond time; 4. The number increase of medical personnel; 5. Doctor’s procedure suitability improvement. Meanwhile, several nursing improvements also need to be taken: 1. Medical personnel’s respond time; 2. The number increase of medical personnel; 3. Medical personnel excellence training. Furthermore, supporting medical services also need improvements: 1. Re-recordkeeping hospital facilities; 2. Hygiene services assessment scheme; 3. Infrastructure improvements for disaster response. Conclusions: PKU Muhammadiyah Bantul Hospital has had preparedness of medical services, nursing and other supporting facilities for disaster management, but there was some elements that need to be improved to reach custumer satisfaction.